Data driven : how performance analytics delivers extraordinary sales results - Dearborn, Jenny (John Wiley & Sons, Inc., 2015)
Data Driven is a uniquely practical guide to increasing sales success, using the power of data analytics. Written by one of the world's leading authorities on the topic, this book shows you how to transform the corporate sales function by leveraging big data into better decision-making, more informed strategy, and increased effectiveness throughout the organization.